A selective and molecular imaging approach for anticancer drug: Pemetrexed by nanoparticle accelerated molecularly imprinting polymer. (10th September 2020) - Ozcelikay, Goksu; Karadas-Bakirhan, Nurgul; Taskin-Tok, Tugba; Ozkan, Sibel A.
Abstract: A new molecularly imprinting polymer (MIP) based sensor was developed for the selective detection of pemetrexed (PMX) by the electropolymerization of ortho phenylenediammine (o-PD) on carbon quantum dot modified screen printed carbon electrode (CQD/SPCE). The surface characterization was performed with cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The conditions such as casting amount of CQD, incubation time, removal time for successful polymerization were tested. The selectivity of developed sensor also tested with similar compounds with PMX. The results showed that the developed sensor could achieve to detection of PMX from synthetic serum sample with high recovery 99.3%. From the computational perspective of view, PMX was also optimized at B3LYP/6-311 G∗//DFT level using the Gaussian 09 program package. Molecular electrostatic potential surface (MESP) was performed to investigate effects of the electronic and structure properties of PMX. Graphical abstract: Image 1 Highlights: The developed sensor had successfully affinity to PMX instead of similar molecules such as guanine, sulpride and ascorbic acid. The surface characterized by surface and electrochemical techniques. Computational applications HOMO–LUMO analysis and MESP were probed by using Gaussian 09.